(untitled) (Raparin Journal of Humanities (RJH), 2026)
This research focuses on the dynamic and fluid identity of the protagonist of The Reluctant Fundamentalist (2007), a novel by Mohsin Hamid (1971-). It claims that the protagonist’s identity is continuously reconstructed with extrinsic and intrinsic ruptures through the lens of postcolonial theory because it provides a framework to analyze identity formation process, particularly the concept of Orientalism by Edward Said (1953-2003) with dual identity and psychological split by Frantz Fanon (1925-1961). The research discusses how the protagonist’s identity is shaped by the global power relations, racial mistrust, and power conflict in America after the 9/11 attacks. It analyzes some of the crucial scenes of the novel and demonstrates how Islamophobia and Western stereotyping generate a crisis in which belonging as well as subjectivity are at stake for Changez in his double consciousness toward resistance. His journey from a New York-based corporate elite to an opponent of American imperialism in Lahore is a tale about decolonizing both political and personal aspects. The form of the novel, as a monologue directed at an American man, emphasizes the ways in which identity shakes under the pressure of fear and suspicion. Furthermore, this research contributes to broader discussions of migrant identity, postcolonial resistance, and the capacity of literature to undermine dominant ways of seeing and treating the Other.